Integrative-interpersonal dynamic therapy for poststroke depression (INID): study protocol of a randomised controlled pilot trial - Volz, Matthias; Mundiyanapurath, Sibu; Schauenburg, Henning; Meuth, Sven; Wild, Beate; Werheid, Katja; Barber, Jacques P.; Schäfer, Ralf; Beerbaum, Luisa; Dinger, Ulrike (BMJ open, 2023)
INTRODUCTION: Depression is the most frequent psychiatric disorder following stroke, affecting about one-third of stroke survivors. Patients experience poorer recovery, lower quality of life and higher mortality compared with stroke survivors without depression. Despite these well-known malign consequences, poststroke depression (PSD) is regarded underdiagnosed and undertreated. Evidence of beneficial effects of psychotherapy to treat PSD remains scarce and inconclusive and is limited by heterogeneity in design, content and timing of the intervention. This pilot study aims to assess the feasibility of a newly developed integrative-interpersonal dynamic PSD intervention in an outpatient setting and provide a first estimation of the potential effect size as basis for the sample size estimation for a subsequent definite trial. METHOD AND ANALYSIS: Patients will be recruited from two German stroke units. After discharge from inpatient rehabilitation, depressed stroke survivors will be randomised to short-term psychotherapy (12 weeks, ≤16 sessions) or enhanced treatment as usual. The manualised psychotherapy integrates key features of the Unified Psychodynamic and Cognitive-Behavioural Unified Protocol for emotional disorders and was adapted for PSD. Primary endpoints are recruitment feasibility and treatment acceptability, defined as a recruitment rate of ≥20% for eligible patients consenting to randomisation and ≥70% completion-rate of patients participating in the treatment condition. A preliminary estimation of the treatment effect based on the mean difference in Patient Health Questionnaire-9 (PHQ-9) scores between intervention and control group six months poststroke is calculated. Secondary endpoints include changes in depression (PHQ-9/Hamilton Depression Scale) and anxiety (Generalised Anxiety Disorder 7) of all participants across all follow-ups during the first year poststroke. ETHICS AND DISSEMINATION: The INID pilot study received full ethical approval (S-321/2019; 2022-2286_1). Trial results will be published in a peer-reviewed journal in the first half of 2025. One-year follow-ups are planned to be carried out until summer 2025. TRIAL REGISTRATION NUMBER: DRKS00030378.